THE INFLUENCE OF CHILDREN LEARNING IN SCIENCE MODELS ON STUDENTS’ SCIENCE PROCESS SKILLS - Nugraha, Febby Fajar; Rahmat, Pupu Saeful; Ramadhina, Vidya (Kopertis Region IV Jabar and Banten, 2023)
Learning that is passive and does not provide direct experience to students is the cause of low students' science process skills. This study aims to determine the effect of the Children Learning In Science learning model on science process skills. This study uses a quantitative approach. The method used in this research is to use a Quasi Experimental Design with the type of pretest-posttest control group design research. The subjects in this study were 33 students in class VA as the experimental class and 29 students in class V B as the control class. The results showed that there were differences in science process skills and differences in improving science process skills between the experimental class. This shows that the Children Learning In Science learning model can have an impact on the science process skills of students who use the Children Learning In Science learning model. Thus, fathers/mothers of teachers who are going to ban science, especially those who want to improve their science process skills, would be a good step, to try to apply the Children Learning In Science learning model.